Ultrasonography of Borderline and Asymmetric Infant Hips - a Challenge in the Management of Developmental Dysplasia of the Hip - Vasilescu, Dan; Cosma, Dan; Vasilescu, Dana Elena; Solomon, Carolina Maria; Corbu, Andrei; Dudea, Sorin Marian (Medicine and Pharmacy Reports, 2018)
Background and aim. Developmental dysplasia of the hip (DDH) is a potentially disabling disease. There are many diagnostic approaches, Graf method ultrasonography being the most popular imaging method. Although considered as a healthy condition, the existence of hips at the 60 degree limit or the asymmetries higher than 4 degrees between left and right side may be a source of unfavorable evolution and consequently of late diagnosed dysplasia cases. Methods. The retrospective study was conducted in the Radiology Department of the Emergency Clinical County Hospital Cluj-Napoca, by retrospective analysis of the database containing 3013 records of the subjects presented for DDH assessment between January 2008 and December 2014. The study focuses on investigating two possible sources of missed cases by clinical-ultrasound management of DDH: borderline and asymmetric hips. Two conditions were studied in patients considered healthy according to Graf method: borderline hips (those with α angle value of 60° and 61°) and asymmetric hips (left to right difference between the α angle values exceeds 4°). Three study groups were formed: healthy subjects, asymmetric/borderline subjects and patients with immature or mild dysplasia. The incidence of risk factors, clinical suspicion and the success of therapy were evaluated. Results. There were no significant differences between the three groups regarding the role of the risk factors in DDH pathogenesis. Data reveal a high suspicion rate after the clinical examination, in groups II and III, compared to the healthy population. This means that from this point of view, Group II might be considered having at least a dysplastic prognosis. An increased correlation in the therapeutic results was observed between Group II patients and those from mild delayed maturation subgroups from Group III (IIa-, IIa+). Conclusions. Asymmetric and borderline hips should be approached similarly to immature hips, clinical suspicion and the therapeutic outcome being similar.